An integrated human resource management model for selected provincial legislatures of South Africa - Mokoena, Amos Judas (Cape Peninsula University of Technology, 2019)
The study was conducted in selected provincial legislatures (Limpopo and Mpumalanga). Provincial legislatures of the Republic of South Africa (RSA) are established in terms of section 43 of the Constitution of the RSA (1996) and draw their mandates from Chapter 6 of the Constitution to pass, amend and repeal legislation that affects their respective provinces. In terms of section 43, provinces are autonomous, distinct and independent. However, they should promote cooperation between and amongst themselves. Presently, there is a lack of or no evidence suggesting that these legislatures are cooperating with each other, at administrative level, in particular in respect of human resource management activities. This causes employees at some legislatures to feel that the treatment of employees is better at other provincial legislatures. This in turn leads to low levels of employee motivation, satisfaction and engagement and to a larger extent a high level of employees intending to leave one provincial legislature for another. The main objective of the study was to develop an integrated human resource management policies and practices model for the similar treatment of employees in provincial legislatures to keep motivation at an acceptable level. There were two other objectives relating to the main problem. Objective 1 was to examine whether there was a significant relationship between the differential application of human resource management policies and practices (Training policies) and employee extrinsic motivation. Objective 2 was to examine whether there was a significant relationship between the differential application of human resource management policies and practices (Salary and decision-making policies) and employee intrinsic motivation. There were two hypotheses relating to the main problem. Hypothesis 1 stated that the differential application of human resource management policies and practices (Training policies) does not contribute significantly to levels of employee extrinsic motivation. Hypothesis 2 stated that the differential application of human resource management policies and practices (Salary and decision-making policies) does not contribute significantly to levels of employee intrinsic motivation. This study used a systematic sampling method to select respondents. The sample selected from the population (N=324) was (n=108). Data collection was through a questionnaire. However, only 90 questionnaires were used (n=90) in this study because thirteen (13) were spoiled and five (5) were not fully completed. The questionnaire met the adequate requirements for construct validity, which was above Cronbach’s alpha 0.5. The capturing of questionnaires was numerically, using Microsoft Excel, and imported into SPSS (Statistical Package for Social Sciences) version 22 (Field, 2009) and AMOS 18 for data analysis. The Structural Equation Model (SEM) proposed for this study was a just-identified model, which had degrees of freedom (28-21). There were 28 distinct sample moments computed and 21 distinct parameters. The Structural Equation Model showed a good fit. Data was analysed using a quantitative process wherein data was summarised using measures of central tendency, such as mean. Furthermore, data was presented using tables, graphs and pie charts. The levels of constructs from the average means were extrinsic motivation 63%, intrinsic motivation 68%, turnover intention 74%, employee satisfaction 68% and employee engagement 66%. The results in respect of the two other objectives of the main problem, namely objective 1 and objective 2, indicated that there was a positive and significant relationship between variables with Path Coefficients output (β = 0.520, ??<0.05) and (β = 0.383, ??<0.05) respectively. Results of the subhypotheses of the main problem, namely subhypothesis 1 and subhypothesis 2, the results indicated that the differential application of human resource management contributed to levels of (1) extrinsic and (2) intrinsic motivation, which produced Path Coefficients output (β = 0.520, ??<0.05) and (β = 0.383, ??<0.05) respectively, Therefore, Null hypotheses for both hypotheses were not supported.
Thesis (DTech (Human Resource Management))--Cape Peninsula University of Technology, 2019
Keywords: Mpumalanga (South Africa). Provincial Legislature -- Personnel management; Limpopo (South Africa). Provincial Legislature -- Personnel management; Legislative bodies -- Officials and employees